Le navettage et la tarification du transport par automobile en milieu urbain - Larin, Gilles (L'Actualité économique)

(untitled) (HEC Montréal, 1980)
AbstractThis article deals with the importance of commuting by automobile in metropolitan areas of Canada. Several characteristics of commuting trips are examined, particularly in the context of trips to work. Existing pricing arrangements are criticized and alternatives suggested. Although no single change would be optimal, some form of cross-subsidization between private and public transportation would improve efficiency.